An Analysis of Prospective Science Teacher Students’ Misconceptions on Photosynthesis and Plant Respiration - Nikmah, Mazroatun; Susilaningsih, Endang; Astuti, Budi (Universitas Negeri Semarang, 2022)
Misunderstanding in drawing conclusions about a concept caused by errors and incomplete thinking is called misconception. The existing misconception can lead to ongoing misconception if it is not immediately corrected. This study aimed to analyze how the level of misconceptions that occured in prospective science teachers. This study was conducted using a mixed-method with an explanatory sequential design. Methods of collecting data were Three Tier Multiple Choice (TTMC) test questions to analyze the misconception and in-depth interview to determine the factors causing misconceptions. The instrument used in this study was TTMC diagnostic test. Technique used for analyzing misconceptions data were descriptive percentages and for analyzing factors causing misconceptions data were in-depth interview. The results show that 60.4% of prospective science teacher students had misconceptions, which means that the misconceptions that occured were in the high category. Factors causing misconceptions were dominated by incompleteness in understanding the material, the influence of previous learning, the references used contain the wrong concept, low interest in deepening the material to find out the correct concept. This study is expected to help teachers and prospective teachers to decide what learning methods can be used to prevent misconceptions. Remediation can be done to find out where the misconceptions occur so that it can be corrected more quickly.